The Study on Use Of Ceramic Waste As Partial Substitute of Fine Aggregates in Cement Bricks - ABU BAKAR, HASNIZA; Johnny Anak Kapok,; Muhamad Hanafi Rahmat,; Emedya Murniwaty Samsudin,; Hannifah Tami, (Recent Trends in Civil Engineering and Built Environment, 2020)
Cement brick is a type of material used in construction work and uses sand as part of its composition. Demand for the use of sand in the construction industry is increasing every year and this can lead to a reduction in natural materials. Meanwhile, ceramic waste has been used as a recycling material in Ayer Hitam, Johor and this can be channeled as a partial substitute of fine aggregates material for future use of sand in the construction industry. This study was conducted to study the strength characteristics of existing cement bricks containing ceramic waste as the partial substitute for fine aggregate. The total replacement percentage of 0%, 5%, 10% and 15% of ceramic waste in a ratio of 1:9 were classified to produce 24 samples of bricks. The tests carried out on the cement brick samples were density tests, water absorption tests and compression strength tests. As a result, the cement brick sample containing 10% ceramic waste had met the standards set out in BS 3921 for the water absorption test and BS 5628 for the compression strength test. The results of the density test showed that the higher the percentage of ceramic waste added to the mix, the density and the weight of the cement bricks decreased. Therefore, cement brick with the substitution of ceramic waste has the potential to become one of the building materials in the construction industry and this helps to reduce total dependence on the sand as a mixture in the cement brick.